Inflammatory Response of Annona Muricata Linn Leaves Extract in Colorectal Cancer Patients - Ingrid Suryanti Surono (Journal of Global Pharma Technology, 2017)
Annona muricata L (AML) is a member of Annonaceae with antioxidant, anti-inflammatory and anticancer properties.  A randomized double blind placebo controlled pre post-trial on twenty colorectal cancer patients who had undergone primary tumor resection were conducted in two groups, each group was supplemented with A. muricata leaves extract, and maltose as placebo. Inflammatory responses were assessed using ELISA method. There is no significant difference between pre and post on cytokine and cyclooxygenase serum level, also between two groups. A strong significant correlation between serum level of TNF-α and IL-10 cytokine (coefficient correlation = 0.64, p = 0.01) and significant correlation between IFN-g and IL-10 (coefficient correlation = 0.47, p = 0.05) was found after 8 weeks AML supplementation, as shown by increasing of IL-10 production, in response to  TNF-α and IFN-γ in an inflammatory condition. This study  is  registered  in Clinical Trials.gov ID:  NCT02439580Keywords: Annona muricata L, inflammatory response, colorectal cancer, cytokine, cyclooxygenase, TNF-α, Interleukin-10, Acetogenin.